The Evaluasi Implementasi Prinsip Good Governance Dalam Pengelolaan Dana Desa Di Desa Kuala Kuayan Kecamatan Mentaya Hulu Kotawaringin Timur - Apriani, Gradila; Sintha, Melia; Aprillina, Iin (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This research aims to evaluate the implementation of good governance principles in Village Fund management in Kuala Kuayan Village, Mentaya Hulu District, East Kotawaringin Regency. The research method used is descriptive qualitative. The results showed that the implementation of good governance principles in Village Fund management in Kuala Kuayan Village has been running, but there are still some obstacles, especially regarding transparency and accountability principles. This research found that community participation in Village Fund planning is quite good, but involvement in supervision is still limited. Transparency of Village Fund budget information is not yet optimal, while accountability for Village Fund reporting has been carried out in accordance with applicable regulations. The effectiveness and efficiency of fund management still need to be improved through more targeted programs. This research recommends the need to strengthen the capacity of village officials, increase socialization of Village Funds to the community, and improve village financial information systems to support transparency and accountability.